The Influence of Attitude, Subjective Norms, Perception of Self-Control And Entrepreneurship Education on Entrepreneurial Intentions - Shandy Aditya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
Over the years, the field of entrepreneurship studies has become important in the world of education (Abdul, Salim, & Kamarudin, 2012). The importance of entrepreneurship can support the view that entrepreneurship has become a major factor in the progress and expansion of the social economy, because it offers more job opportunities, as well as the impact on national growth and income distribution in a country (Ali, Topping, & Tariq, 2010). Many studies have shown the interaction between entrepreneurship education and entrepreneurial intentions (Gerba et al., 2012; Kurniawan, 2013; Hassan and Wafa, 2012; Noel, 2001; Paco et al. 2012; Widawati, 2012; Schlaegel and Koenig, 2014). The aim of this study was to empirically examine factors such as personal attitudes, subjective norms, perceptions of self-control and entrepreneurial education that stimulate entrepreneurial intentions during higher education programs using data collected on campus. This research examines attitudes, norms, self-control, and entrepreneurship education on entrepreneurial intentions. The research test used multiple linear regression analysis techniques with the help of the SPSS 23 program. Where the number of respondents in this study were 95 students of the Jakarta State University Management Study Program. Based on the results of the study, it can be seen that the research results show that the variable personal attitude affects entrepreneurial intention, self-control variable affects entrepreneurial intention, and the entrepreneurship education variable does not influence entrepreneurial intention.